Interactions Between Light Intensity and Phosphorus Nutrition Affect the P Uptake Capacity of Maize and Soybean Seedling in a Low Light Intensity Area - Zhou, Tao; Wang, Li; Li, Shuxian; Gao, Yang; Du, Yongli; Zhao, Li; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2019)
To capture more nutrients, root systems of maize (Zea mays L.) and soybean (Glycine max L.) exhibit morphological and physiological plasticity to a localized supply of phosphorus (P). However, the mechanisms of the interaction between light intensity and P affecting root morphological and physiological alterations remain unclear. In the present study, the regulation of P uptake capacity of maize and soybean by light intensity and localized P supply was investigated in a low solar radiation area. The plants were grown under continual and disrupted light conditions with homogeneous and heterogeneous P supply. Light capture of maize and soybean increased under the disrupted light condition. Plant dry weight and P uptake was increased by more light capture, particularly when plants were grown in soil with heterogeneous P supply. Similarly, both localized P supply and disrupted light treatment increased the production of fine roots and specific root length in maize. Both homogeneous P supply and disrupted light treatment increased the malate and citrate exudation in the root of soybean. Across all of the experimental treatments, high root morphological plasticity of maize and root physiological plasticity of soybean were associated with lower P concentrations in leaves and greater sucrose concentrations in roots. It is suggested that the carbon (C), exceeded shoot growth capabilities and was transferred to roots as sucrose, which may serve as both a nutritional signal and a C-substrate for root morphological and physiological changes.